IoT-Based Recycle Rebate System – Securing Website and Database - Husin, Husna Sarirah; Mohamad Fairuz, Azatulnajihah; Beh, Delina (Journal of Computing Technologies and Creative Content, 2020)
Web database is a database application that is designed to be managed and accessed through the Internet and has gained the trust of clients and users over the globe. But without having a proper security implementation towards the web database, users and clients may lose trust. To mitigate them, we approach the problem by following the process of security assessment.  In this paper, we introduce security assessment method through Vulnerability Assessment and Penetration Testing Process and Risk Matrix results to find the vulnerabilities and threats on the website and database of the Recycle Rebate System. The implementation of mitigation method used are based on the results scanning of the VAPT process and the Risk Matrix Table. All the results of the VAPT scanning were documented into a Risk Assessment Report which calculate the risk level of each existing results found and can be easily viewed and understand in the table form named Risk Matrix.